Hands-On Penetration Testing on Windows : Unleash Kali Linux, PowerShell, and Windows debugging tools for security testing and analysis /: Unleash Kali Linux, PowerShell, and Windows debugging tools for security testing and analysis. (2018) - Bramwell, Phil
No abstract available